A Review of Coconut Shell-Based Activated Carbon as a Context for Teaching Material and Thermal Physics - Wahyuna Nur (Physics Education, 2026)
The study of physics is often considered abstract because it is not sufficiently linked to real-world phenomena in everyday life. Therefore, contextual learning resources are needed that can connect physics concepts to the surrounding environment. One topic with potential for development in physics education is the production of biomass-based activated carbon through physical activation methods. This article aims to review various studies on the production of activated carbon using physical activation and to analyze its relationship with physics concepts. The research method employed was a literature review of national and international articles on carbonization, activation using steam, CO₂, and microwaves, as well as the characterization of activated carbon. The results of the study indicate that the activated carbon production process involves concepts of heat, thermodynamics, gas diffusion, material structure, and adsorption. Physical activation using steam or CO₂ at temperatures of 750–800°C results in better pore development and adsorption capacity. Additionally, characterization using SEM, BET, FTIR, and XRD can serve as an introduction to modern physics instrumentation. This study indicates that the production of biomass-based activated carbon has the potential to serve as a contextual learning resource in physics education through project-based learning and the STEM approach.